Pengembangan Literasi Keuangan Berbasis Website dalam Meningkatkan Inklusi Keuangan Menuju Indonesia Emas 2045 - Muhammad Ichwan Musa; Muhammad Ilham Wardhana Haeruddin; Aslam, Annisa Paramaswary; Aswar, Nurul Fadilah; Abadi, Rahmat Riwayat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This community service project aims to develop a financial literacy website designed to improve the financial understanding of the Indonesian population, focusing on the key elements necessary for user engagement. The study adopts a mixed-methods approach, combining quantitative data from online surveys and qualitative insights from in-depth interviews and group discussions. The findings reveal that variables such as age, gender, education level, and marital status significantly influence financial literacy and investment decisions. Younger individuals and those with higher levels of education demonstrate superior financial literacy, which in turn affects their investment choices. Additionally, individuals residing in urban areas and those who are married tend to exhibit higher financial literacy. Based on these findings, the project team identified essential user needs, including easy access to information, responsive functionality, and relevant content. The website was developed using technologies such as HTML, CSS, PHP, and CMS to ensure optimal accessibility. Prior to the official launch, comprehensive testing was conducted to verify the website's functionality and compatibility across various devices and browsers. This study contributes to the advancement of financial literacy in Indonesia, with the expectation that the website will support informed investment decisions and contribute to the improvement of economic well-being.